O potencial termal de Águas de São Pedro/SP: o resgate do balneário como incentivo para o turismo - Alves, Júlia Hebling [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The use of water as a therapeutic agent has been carried out for more than five thousand years in several civilizations, such as the Greek and Roman civilizations, which developed hydrotherapy, emphasizing its important social and therapeutic function. The spas were places with a focus on keeping the body and mind healthy, through leisure at work, practice of physical, artistic or intellectual activities. Keeping healing and leisure in the same environment. Thermalism is an ancient and natural therapeutic practice of alternative treatment in which mineral waters can be used in therapies and treatments due to its variety of special components. Social thermalism and crenotherapy are recognized in the Unified Health System (SUS) as integrative and complementary practices, thus guaranteeing the right of access to users. Because of this, such practices are found in the SUS as observatories, certainly due to their little use, the lack of training of specialized professionals to work in the area or the current lack of self-funding models in the SUS for these practices, in addition to other reasons. Water resources and tourism are interconnected with hydrotherapy, as they are sources of access that lead to therapeutic practice. In addition, it provides a range of new possibilities for therapeutic searches that can bring great benefits to the population and also enables the development of public policies aimed at alternative treatments, in particular the integration of man with nature, which favors the results of treatments in health.

O aproveitamento da água como agente terapêutico é realizado há mais de cinco mil anos em diversas civilizações, como por exemplo a Grega e a Romana que desenvolveram o termalismo ressaltando sua importante função social e terapêutica. As termas eram locais com foco em manter o corpo e a mente sãos, por meio do ócio do trabalho, da prática de atividades físicas, artísticas ou intelectuais. Mantendo cura e lazer no mesmo ambiente. O termalismo é uma prática terapêutica milenar e natural de tratamento alternativo em que águas minerais podem ser usadas em terapias e tratamentos devido a sua variedade de componentes especiais. O termalismo social e a crenoterapia são reconhecidos no Sistema Único de Saúde (SUS) enquanto práticas integrativas e complementares, sendo, portanto, garantido o direito de acesso aos usuários. Por conta disso, tais práticas se encontram no SUS como observatórios, certamente devido a seu pouco uso, pela pouca formação de profissionais especializados para atuarem na área ou pela inexistência atual de modelos de financiamento próprio no SUS para essas práticas, além de outros motivos. Os recursos hídricos e o turismo estão interligados ao termalismo, pois são fontes de acesso que levam à prática terapêutica. Além disso, proporciona um leque de novas possibilidades de buscas terapêuticas que podem trazer ótimos benefícios para a população e possibilita ainda o desenvolvimento de políticas públicas voltadas para tratamentos alternativos, em especial na integração do homem com a natureza, que favorece os resultados dos tratamentos na saúde.
The thermal potential of Águas de São Pedro/SP: the rescue of the spa as an incentive for tourism
Keywords: Termas; Água mineral; Estâncias hidrominerais; Health spas; Turismo médico